CHI '13 Extended Abstracts on Human Factors in Computing Systems 2013
DOI: 10.1145/2468356.2468695
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of 20 web form optimization guidelines

Abstract: Most websites use interactive online forms as a main contact point to users. Recently, many publications aim at optimizing web forms. In contrast to former research that focused at the evaluation of single guidelines, the present study shows in a controlled lab experiment with n=23 participants the combined effectiveness of 20 guidelines on real company web forms. Results indicate that optimized web forms lead to faster completion times, less form submission trials, fewer eye fixations and higher user satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Note that preliminary data on this study has been presented as "Work-in-progress" at CHI 2013 [28]. In comparison to this publication, we expand these data by investigating more participants and extending our analysis of user performance data (error analysis, eye tracking data, Keystroke Level Model comparison) and of questionnaire data and interviews.…”
Section: Acknowledgmentsmentioning
confidence: 94%
“…Note that preliminary data on this study has been presented as "Work-in-progress" at CHI 2013 [28]. In comparison to this publication, we expand these data by investigating more participants and extending our analysis of user performance data (error analysis, eye tracking data, Keystroke Level Model comparison) and of questionnaire data and interviews.…”
Section: Acknowledgmentsmentioning
confidence: 94%
“…Such requirements capture the input data that shall be collected for certain types of users; they are fulfilled by setting the required/optional property of the corresponding fields in a data entry form. In other words, the required fields (also called mandatory fields [46]) of a form collect input information considered as important to the stakeholders who plan to use the collected information; the absence of this information could affect the application usage. On the contrary, optional fields collect information that is nice to have but whose absence is acceptable.…”
Section: Data Entry Formsmentioning
confidence: 99%
“…Designing user-friendly form fields is one of the most critical aspects of overall user experience with Web forms . Web forms lacking usability result in a significant level of user dissatisfaction thus increasing the drop-out rate, preventing the collection of the required data (Seckler, Heinz, Bargas-Avila, Opwis & Tuch, 2013), and decreasing the number of logins to a Web application (Thompson & Torabi, 2007). The usability of form fields vary greatly depending on how they are designed, but minor changes to the form design make it possible to increase the interaction speed, reduce user errors, and improve user satisfaction (Seckler et al, 2014).…”
Section: Web Formsmentioning
confidence: 99%
“…Das, McEwan, and Douglas (2008) used an eyetracking system to examine the usability of label positions in Web forms and found that right-aligned labels provided the shortest completion time. In another study conducted with 23 participants, optimized Web forms were found to produce faster data entry, fewer errors, less eye fixation, and higher user satisfaction (Seckler et al, 2013). In their usability study, Strohl et al (2015) optimized the design of existing forms according to the following facets of user experience: usefulness, usability, accessibility, credibility, findability, and desirability.…”
Section: Eye-tracking Research In Web Formsmentioning
confidence: 99%